Contribuição para o desenvolvimento de uma metodologia de avaliação da eficiência no setor de transmissão de energia elétrica - Andrade, Gustavo Naciff de (2010)
This study starts with a presentation of a benchmarking methodology proposed by ANEEL (2009) for operating costs of the main electricity transmission companies in Brazil. The model proposed uses Data Envelopment Analysis (DEA) in two phases with the inclusion of environmental factors using multiple regression in the second stage. The study also proposes a different approach with respect to the efficiency calculation, using the probabilistic composition model developed by Sant´Anna (2002), and also by replacing the second stage proposed by the regulator by using the Malmquist index for assessment of developments in corporate efficiency on the horizon of time analyzed. Also it is the aim of the study to understand the main factors that may affect the efficiency of the firms studied, and to compare the different approaches presented.